Simulation of the dynamics of the Hansbreen tidal glacier (Svalbard) based on the stochastic model - A. V. Kislov; A. F. Glazovsky (Лëд и снег, 2019)
The dynamics of the Hansbreen tidal glacier (Svalbard) is manifested at different time scales. In addition to the long-term trend, there are noticeable inter-annual fluctuations. And the last ones are precisely the subject of this work. Based on general conclusions of the theory of temporal dynamics of the massive inertial objects, the observed inter-annual changes in the length of the glacier can be explained as a result of the accumulation of anomalies of the heat fluxes and water flows. In spite the fact that the initial model of glacier dynamics is deterministically based on the physical law of conservation of ice mass (the so-called the «minimal model» was used), the model of length change is interpreted as stochastic. From this standpoint, it is the Langevin equation, which includes the effect of random temperature anomalies that can be interpreted as a white noise. From a mathematical point of view, this process is analogous to Brownian motion, i.e. the length of the Hansbreen glacier randomly fluctuates in the vicinity of its stable equilibrium position. Based on the Langevin equation, we passed to the Fokker–Planck equation, the solution of which allowed us to obtain the distribution function of the probabilities of interannual fluctuations of glacier length, which is close to the normal law. It was shown that the possible range of the variability covers the observed interval of the length fluctuations. The pdf is close to normal distribution.